PENGARUH IKLAN DAN PERILAKU KONSUMTIF TERHADAP KEPUTUSAN PEMBELIAN MELALUI MARKETPLACE SHOPEE - Suri Juwita (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
The purpose of this study's findings is to understand how advertisements and consumer behavior relate to the reasoning behind purchases made through the market place shopee. The entire 7th semester population Jurusan Management of the business and economics faculty Economic Development course is represented in this essay. In this study, 63 people who bought skincare products from an underpriced store were sampled, and they were interviewed informally using the method of random sampling. These kinds of analysis is a quantitative analysis. Iklan and consumer behavior are taken into account while using the data collection tools, angket and pengamatan langsung kelapangan, which are after which it was examined utilizing a linear regression analysis. technique Y=3,332 + 0,547 X1 +0,504 X2 + e, which is intended to better understand the reasons behind purchases. To conclude, pengujian with uji hipotesis has resulted in Fhitung 55,429>3,15, allowing it to be demonstrated that every variable X is simultaneously changing in response to the thesis of the study. Uji t presents 4,447>1,67 and 4,164>1,66, which are advertisements and consumer behavior with significant bearing on the case for purchase. R square indicates that the coefficient of determination is approximately 0.64, meaning that advertisements and Consumer actions have a big influence on the likelihood of purchase being made, which is approximately 64,9%. In contrast, sisanya has a significant impact of approximately 35,1 on other factors That was not examined in this research The purpose of this study's findings is to understand how advertisements and consumer behavior relate to the reasoning behind purchases made through the market place shopee. The entire 7th semester population Jurusan Management of the business and economics faculty Economic Development course is represented in this essay. In this study, 63 people who bought skincare products from an underpriced store were sampled, and they were interviewed informally using the method of random sampling. These kinds of analysis is a quantitative analysis. Iklan and consumer behavior are taken into account while using the data collection tools, angket and pengamatan langsung kelapangan, which are after which it was examined utilizing a linear regression analysis. technique Y=3,332 + 0,547 X1 +0,504 X2 + e, which is intended to better understand the reasons behind purchases. To conclude, pengujian with uji hipotesis has resulted in Fhitung 55,429>3,15, allowing it to be demonstrated that every variable X is simultaneously changing in response to the thesis of the study. Uji t presents 4,447>1,67 and 4,164>1,66, which are advertisements and consumer behavior with significant bearing on the case for purchase. R square indicates that the coefficient of determination is approximately 0.64, meaning that advertisements and Consumer actions have a big influence on the likelihood of purchase being made, which is approximately 64,9%. In contrast, sisanya has a significant impact of approximately 35,1 on other factors That was not examined in this research